Nano-structure made of donor-acceptor quantum dots embedded in three dimensional photonic crystals for all optical tunable quantum memory/switch applications. (15th August 2021) - Hezarjaribi, Mahdi Khalili; Mollabashi, Mahmoud; Razi, Sepehr
Abstract: A robust, energy efficient, tunable as well as self-directed quantum structure made of two different sized QDs is proposed for switching and memory applications in quantum photonics. Three dimensional photonic crystal (PC) made of nonlinear polystyrene spheres is considered as the substrate to carry the closely located dots. Theoretical model based on density matrix approach is introduced to evaluate the physical features of the proposed system by taking in to consideration of the near field optical energy transfers whose spatial nature is characterized by a Yukawa-type potential. Furthermore, all couplings of excitons to thermal bath besides of the possible intra-dot relaxations are considered in modellings. Probabilities of the quantum states and switchings in between the states are studied systematically over time by exploring the populations of 8 possible configurations. In order to better understand the potential of the suggested structure to be utilized as a tunable quantum element, dependence of the possible absorption/dispersions and the population of each quantum state, to the structure temperature and features of the illuminating lights are discussed in detail. Results clearly reflect that energy transfer in subwavelength range is possible using the suggested system via combined effects of near field interactions and relaxations of energy levels. Then this study provides insight into design and fabrication of structures based on network of QDs embedded in PC that are both self-tunable as well as being controllable using external factors and thus meet the goals of integrated photonic circuits.